Strategi Promosi Produk dalam Menghadapi Persaingan di Era Modernisasi - Susanti; Muhammad Hifdil Islam; Moh Abd Rahman (SAFE-Network, 2024)
The era of globalization is an era marked by rapid development in all fields, both in trade and other fields. The changes that occur are marked by the developing mindset of society, advances in technology, and lifestyles that cannot be separated from the influence of globalization. Changes in the business environment are also increasingly uncertain because many companies are being founded this is one of the triggers for increasingly sharp competition in the business world. The purpose of this article is to analyze what promotional strategies are carried out by the Yaumi S 47 store so that it continues to exist and can compete in the are of modern retail companies that are not far from the location of the store, such as Indomaret, Alfamart, and Supermarkets. This research takes the form of a descriptive qualitative approach. The type of research carried out is field research. The results of this research show that the Yaumi S 47 Store has several promotional strategies that can attract consumer interest so that it can maintain the existence of the store by keeping up with current developments. The promotional strategy is to increase income and maintain the sustainability of the store so that it always experiences development every year.